Rubber tree early selection for yield stability in time and among locations - Gouvêa, Lígia Regina Lima; Silva, Guilherme Augusto Peres; Verardi, Cecília Khusala; de Oliveira, André Luis Bombonato; Gonçalves, Elaine Cristine Piffer; Scaloppi-Junior, Erivaldo José; de Moraes, Mário Luiz Teixeira; de Souza Gonçalves, Paulo (Springer Nature, 2013)
Rubber production in the rubber tree [Hevea brasiliensis (Willd. ex Adr. de Juss.) Muell. Arg.] can be expressed differently in different environments. Thus the objective of the present study was to select productive progenies, stable and responsive in time and among locations. Thirty progenies were assessed by early yield tests at three ages and in three locations. A randomized block design was used with three replications and ten plants per plot, in 3 × 3 m spacing. The procedure of the mixed linear Reml/Blup model-restricted maximum likelihood/best non-biased linear prediction was used in the genetic statistical analyses. In all the individual analyses, the values observed for the progeny average heritability (ĥpa 2) were greater than those of the additive effect based on single individuals (ĥa 2) and within plot additive (ĥad 2). In the joint analyses in time, there was genotype × test interaction in the three locations. When 20 % of the best progenies were selected the predicted genetic gains were: Colina GG = 24.63 %, Selvíria GG = 13.63 %, and Votuporanga GG = 25.39 %. Two progenies were among the best in the analyses in the time and between locations. In the joint analysis among locations there was only genotype × location interaction in the first early test. In this test, selecting 20 %, the general predicted genetic gain was GG = 25.10 %. Identifying progenies with high and stable yield over time and among locations contributes to the efficiency of the genetic breeding program. The relative performance of the progenies varies depending of the age of early selection test. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Early yield tests; Genetic parameters; Hevea brasiliensis; Reml/Blup; Repeated means